Testing an IEC 61850-based light-weighted controller for reactive power management in smart distribution grids - Sirviö, Katja; Mekkanen, Mike; Kauhaniemi, Kimmo; Laaksonen, Hannu; Salo, Ari; Castro, Felipe; Ansari, Shoaib; Babazadeh, Davood (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Due to the large-scale integration of distributed energy resources (DER) new options for the local and system-wide technical ancillary services are needed. Reactive power control is one of such ancillary service provided by DERs. This paper aims to test the performance of a reactive power control scheme developed on a light-weight Intelligent Electronic Device (IED). The IEDs are implemented on a BeagleBoneBlack as well as on an FPGA. The test set-up is implemented by the Controller-Hardware-In-the-Loop platform. The simulation platform is OPAL-RT's eMEGASIM and ePHASORSIM. The results show the performance of the FPGA to be better than BeagleBoneBlack when comparing results of the Sofware-In-the-Loop simulations.
Keywords: control systems; microgrids; power system simulation; testing; fi=Sähkötekniikka|en=Electrical Engineering|